PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI IN HOUSE TRAINING (IHT) DI SMPN 1 SUNGAI TARAB - Chandra, Doni (STKIP Pesisir Selatan, 2018)
Based on the results of observations and supervision carried out by the author, the teacher's pedagogical competence in preparing lesson plans is still low. The purpose of this study was to describe and obtain information about the Improvement of Teacher's pedagogic competencies in Developing Learning Implementation Plans (RPP) Through In House Training (IHT) at Tarab River 1 Junior High School. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subject consisted of 4 teachers who taught at Tarab River 1 Junior High School. The research data was collected using observation sheets. Data were analyzed using percentages. The results of the study indicate that the implementation of the In House Training (IHT) can improve the pedagogical competence of the teacher in preparing lesson plans. This is evidenced by the value of the initial teacher competency before the program is 74. Then after IHT activities there is an increase in the first cycle is 78.70 (good) and after that increases in cycle II to 87.56 (Very good)